1986
DOI: 10.1046/j.1537-2995.1986.26486262736.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of unrelated persons as bone marrow donors. A preliminary experience

Abstract: Seven hundred and sixty-three blood donors previously typed for HLA-A and B antigens were asked to consider donating bone marrow to unrelated patients for whom no HLA-matched sibling was available. Eighty-eight percent (668) indicated willingness to donate marrow, and of these, 615 (81%) participated in testing and 53 (7%) were unable to participate at the time of the request. Donors matched for HLA-A, B, C, and DR antigens and compatible in the mixed-leukocyte culture reaction were identified for 12 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 16 publications
0
15
0
3
Order By: Relevance
“…Its principles and policies are basically similar to those of the marrow donor registries in the United States and European countries. 17,34,35 JMDP involves 68 local blood centers for the HLA class I and II serological typing of volunteer donors and involves the central blood center for the accumulation of this HLA information for matching to registered patients and for HLA DNA typing among HLA serologically-matched pairs. JMDP has also approved 129 units in 101 institutes experienced in allogeneic BMT as transplant and harvest centers distributed throughout the country.…”
Section: Jmdpmentioning
confidence: 99%
“…Its principles and policies are basically similar to those of the marrow donor registries in the United States and European countries. 17,34,35 JMDP involves 68 local blood centers for the HLA class I and II serological typing of volunteer donors and involves the central blood center for the accumulation of this HLA information for matching to registered patients and for HLA DNA typing among HLA serologically-matched pairs. JMDP has also approved 129 units in 101 institutes experienced in allogeneic BMT as transplant and harvest centers distributed throughout the country.…”
Section: Jmdpmentioning
confidence: 99%
“…Such studies found mixed results regarding the relationship between previous apheresis and willingness to donate BM, and no consistent demographic predictors of donor intentions. [6][7][8][9] Later research revealed that donor attitudes and behaviors were complex phenomena shaped both by pro-donation factors, such as altruism and social desirability, and anti-donation factors, such as distrust of the medical system and religious values. [10][11][12] Although this research yields information about the types of individuals who may donate marrow and stem cells, focusing solely on such stable psychological and personality characteristics obscures the fact that donor attitudes can also be affected by education 5 and persuasive communications.…”
Section: Introductionmentioning
confidence: 99%
“…Starting in 1986 BM donor registries were created in both the USA and Europe. 7,8 Since then, BM donor registries have been created world-wide, enrolling millions of volunteer donors with thousands of BM collected; [9][10][11][12][13] there are currently 46 registries located in 36 countries, counting for 6.5 million potential BM donors (last up-date June 2000). The Italian Bone Marrow Donor Registry (IBMDR) was created in 1989 and there are currently 270 000 enrolled donors with 700 BM collections already performed (last up-date October 2000).…”
mentioning
confidence: 99%